KEBIJAKAN DAN STRATEGI PENINGKATAN KOMPETENSI GURU SERTA RELEVANSINYA TERHADAP MUTU LULUSAN YANG ISLAMI - Maskuri Ismail; Khairul Anwar (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
teacher as the first position in reaching educational vision and mission, because of that teacher has an important role to upgrade their quality. Besides that, teacher has to enhance their competence. So has many implementer policies of national education system released to support teacher's competence enhancement. Donations, education facilities, training allocated for teachers by country be an opportunity to make innovative and creative work. Teacher be approved by the nation not only limited at legal formal, but also by providing financial right as appreciation for great earnings. By the several teacher's competencies, including holistic, integrative, religious, so that institutional education will produce qualified graduates, competitive, independence, and responsibility to solve educational problems, like moral decadention. To make easier for teacher competency improvement strategies, so school as one of the institutional education has to do better planning through the process of analysis. The totality of school or madrasah management can produce good and correct quality education.